Analysis of the Influence of the Harbor Master's Function in Supervision of Ship Safety and Security Management in the Ksop Class III Tanjung Pakis Area - Febriansyah, Gear Sharp; Kurniawan, Edi; Rahayu, Trisnowati; Dahri, Muhammad (Politeknik Ilmu Pelayaran Semarang, 2024)
Sea transportation is a means of transportation that has a very vital role as a means of transportation that can reach all regions via water. In order for activities to run smoothly, good ship safety and security management efforts are needed. The management efforts are external, namely supervising ship activities by the KSOP harbormaster. The aim of this research is to find out and analyze the influence of the harbormaster's function in supervising the management of ship safety and security in the KSOP Class III Tanjung Pakis. The research method used in this research is a quantitative method using the SPSS application. The number of samples in this research was 50 crew members who were active in the KSOP Class III Tanjung Pakis area using the Non-Probability Sampling method with the Quota Sampling Technique. The analysis technique used in this research is simple linear regression analysis, then the equation results are obtained, namely Y = 19.969 + 0.398X. The results of this research show that harbormaster supervision has a positive and significant effect on ship safety and security management in the KSOP Class III Tanjung Pakis area. Then, based on the test results, the coefficient of determination showed a result of 0.783, which means that the influence of the harbormaster's supervision on ship safety and security management in the KSOP Class III Tanjung Pakis area is 78.3%